(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
International students may face more pressure due to cultural differences that cause culture shock, which generates many thought-provoking phenomena. Not only the negative misunderstanding evaluation of the international students, but some of them may also be put into danger or even life-threatening because of lacking overseas culture knowledge. This research aimed to help international students overcome the dissatisifaction of life, which caused by conflicts between self-consciousness and new information under the previous personal schema. It takes time for the personal schema to adjust to processing new information which appears in culture shock. Meanwhile, the research shows that adjust self-consciousness timely accord to environment changes can improve the satisfaction of life through continually self-reflection, whereby providing a new path for international students to ultimately improve overseas life satisfaction. The research was Structural Equation Model to analysis cross-sectional data collected with judgment sampling method from Chinese international students study in Study Abroad through Chinese Program (SACP), to veriyft the proprsed model. Chinese international students had studying experience in Thailand universities from 6 monthes to 3 years. The result shows that CQ plays a positively moderate role in the process of self-consciousness to self-reflection. Besides, this study mainly discusses the importance of improving self-consciousness and self-reflection for international students to live abroad, which is rarely mentioned before. The findings of this research show that international students need CQ training to help to adjust their personal schema so that they can integrate into the local life faster and find orientation in the heterogeneous culture.